Integrative analysis of transcriptome and lipidome reveals fructose pro-steatosis mechanism in goose fatty liver - Wei, Rongxue; Han, Chunchun; Wei, Shouhai; Teng, Yongqiang; Li, Liang; Liu, Hehe; Hu, Shengqiang; Kang, Bo; Xu, Hengyong (Frontiers in Nutrition, 2023)
To further explore the fructose pro-steatosis mechanism, we performed an integrative analysis of liver transcriptome and lipidome as well as peripheral adipose tissues transcriptome analysis using samples collected from geese overfed with maize flour (control group) and geese overfed with maize flour supplemented with 10% fructose (treatment group). Overfeeding period of the treatment group was significantly shorter than that of the control group (p < 0.05). Dietary supplementation with 10% fructose induced more severe steatosis in goose liver. Compared with the control group, the treatment group had lower in ceramide levels (p < 0.05). The key differentially expressed genes (DEGs) (control group vs. treatment group) involved in liver fatty acid biosynthesis and steroid biosynthesis were downregulated. The conjoint analysis between DEGs and different lipids showed that fatty acid biosynthesis and steroid biosynthesis were the highest impact score pathways. In conclusion, fructose expedites goose liver lipid accumulation maximization during overfeeding.